(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Abstract: The aim of this study was to evaluate the role of ultrasound in evaluation of patients with focal hepatic mass lesions, to study the imaging spectrum of focal hepatic lesions, to study the relative prevalence of different focal hepatic mass lesions, and to correlate the ultrasound findings with FNAC and/or CT scan.Methods: The study was prospective and was carried out between December 2018 and April 2019 at the Department of Radiology, AMC MET Medical College and Sheth L.G.Hospital, Ahmedabad. Total 100 patients having focal hepatic mass lesions diagnosed on ultrasound and findings confirmed either on CT scan or ultrasound guided aspiration cytology were included in the study. Confirmation of diagnosis either by CT Scan or ultrasound guided FNAC done prior to data collection.(Only those patients are included whose ultrasound diagnosis was confirmed either by ultrasound guided FNAC or CT scan already done.)Results: Out of 100 patients diagnosed by ultrasound, the most common focal hepatic mass lesions seen in our study were- liver abscess, hemangiomas, hydatid cysts, metastasis, primary liver tumors and focal areas of contusions/hematoma. Correlating with FNAC and/or CT scan, ultrasound had an average specificity of 94%, with 100% specificity for common benign lesions like hemangiomas.Conclusion: Ultrasound is a safe and effective method of detecting focal liver lesion. Its low cost, easy availability and lack of ionizing radiation and iodinated contrast media makes it most ideal for imaging the liver. It aids in defining therapeutic decision quickly and allows ultrasound guided interventions. High degree of specificity of ultrasound diagnosis in the present study confirms the value of ultrasonographic evaluation of focal liver lesions and suggests that it can be effectively used in the routine diagnostic work.